2023
DOI: 10.1021/acsearthspacechem.3c00155
|View full text |Cite
|
Sign up to set email alerts
|

Ultraviolet Irradiation Can Increase the Light Absorption and Viscosity of Primary Brown Carbon from Biomass Burning

Habeeb H. Al-Mashala,
Katrina L. Betz,
Colton T. Calvert
et al.

Abstract: The light absorption of brown carbon (BrC) constituents of biomass burning organic aerosol (BBOA) changes in the atmosphere, in part due to multiphase oxidation. For example, ozonolysis leads to the whitening of primary BrC constituents. Irradiation can also change the properties of BrC. Here, we investigate the interplay between irradiation and multiphase processing by measuring the reactive uptake of ozone to thin films of BBOA before and after exposure to UV radiation in a photoreactor. Thin films were prep… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1
1

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(5 citation statements)
references
References 74 publications
0
5
0
Order By: Relevance
“…Current atmospheric models that treat biomass burning organic aerosols typically consider them as single-phased particles. 37,[47][48][49] The results herein show that BBOA, at least in regions where forests primarily consist of pine trees, should be treated as having two separate phases. Depending on the degree of internal/external mixing of organic aerosol in forest fire plumes, these two phases may coexist and be separated within individual particles.…”
Section: Discussionmentioning
confidence: 71%
See 2 more Smart Citations
“…Current atmospheric models that treat biomass burning organic aerosols typically consider them as single-phased particles. 37,[47][48][49] The results herein show that BBOA, at least in regions where forests primarily consist of pine trees, should be treated as having two separate phases. Depending on the degree of internal/external mixing of organic aerosol in forest fire plumes, these two phases may coexist and be separated within individual particles.…”
Section: Discussionmentioning
confidence: 71%
“…45,46 Despite the above, models simulating the chemistry, transport, and climatic impacts of wildfire BBOA typically assume that BBOA comprises only a single phase. 37,[47][48][49] Our understanding of the viscosity and phase behaviour of BBOA remains incomplete, in part, because previous studies have focused on samples generated in the laboratory and not collected from the real atmosphere. The composition of BBOA in the real atmosphere may be different than the composition of BBOA in the laboratory for several reasons including atmospheric aging of BBOA, higher degrees of dilution, and burning conditions (e.g.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Moreover, the expected increase in mixing the time scales of organic compounds in solid-like particles due to hindered bulk diffusion coefficients affects atmospheric multiphase reaction chemistry . More rigid, viscous aerosols undergo slower photochemical transformations and ozonolysis, , contributing to their chemical inertness as they disperse away from the emission source. This inertness can further amplify their absorbance contribution in radiative forcing processes, making them a crucial factor in understanding and modeling Earth’s climate system.…”
Section: Atmospheric Implicationsmentioning
confidence: 99%
“…For example, high-molecular-weight BrC compounds have been observed to be less susceptible to photodegradation than lower molecular weight compounds. , Another study discovered that photolyzed BrC species featured higher oxidation state values and lower molecular weights, demonstrating photooxidation aging mechanisms during long-range transport . Recent laboratory studies have also reported changes in the composition and reactivity of BrC mixtures resulting from the evaporation of their components. However, establishing a predictive understanding of BrC’s molecular composition and light absorption properties is yet incomplete, necessitating additional comprehensive studies. Notably, even trace amounts of strongly absorbing chromophores can contribute significantly to the overall optical properties of the bulk BrC material. ,,,,, Therefore, elucidating this intricate relationship requires the application of complementary multimodal analytical techniques that can measure both component-specific and bulk BrC properties.…”
Section: Introductionmentioning
confidence: 99%